PERTANGGUNGJAWABAN MENGENAI STATUS PERBUATAN HUKUM TERHADAP PERSEROAN TERBATAS (PT) YANG BELUM RESMI BERDIR - Hakim, Ovaldo Noor; Sumeru, Fayuthika Alifia Kirana; Dumais, Alvaro David Gabriel; Andryawan, Andryawan (Jurnal Hukum Adigama, 2021)
In the 1945 Constitution of the Republic of Indonesia Article 1 paragraph (3) which reads "Indonesia is a state of law" so that the public is obliged to obey the applicable regulations. The creation of legal certainty is one of the goals of the rule of law. The ratification of a legal regulation by the community carried out and made by a notary is also included in the achievement of legal certainty. As is the case with the establishment of a Limited Liability Company, therefore it is necessary to make a deed of establishment by a notary, but what if the Limited Liability Company does not yet have official status as a legal entity, then the liability of the Limited Liability Company is required because every activity has legal consequences for those who have a business. Considering that Indonesia is a legal state, everything that results in legal actions must also be resolved through legal channels so that it can be said to be legal as a legal act.